Genotyping and characterization of two polymorphic microsatellite markers located within introns 29 and 30 of the human thyroglobulin gene - Rivolta, Carina Marcela (2002)
The purpose of the present work was to characterize two new polymorphic microsatellite markers in the thyroglobulin gene. TGrI29 and TGrI30 repeats are located within introns 29 and 30, respectively. Genetic studies were carried out by using polymerase chain reaction (PCR) followed by denaturing polyacrilamide gel electrophoresis. TGrI29 exhibited clearly 4 distinguishable alleles ranging from 197 to 203 base pair (bp) in length and TGrI30 showed 8 alleles ranging from 502 to 542 bp. We characterized the two markers by determinating allele frequencies and measures of variation. The heterozygosities (HET) observed of TGrI29 and TGrI30 were 0.859 and 0.522, respectively. The polymorphism information contents (PIC) were 0.471 and 0.434, respectively. No significant differences from Hardy-Weinberg values were found for these two systems. The PCR products of each allele were cloned using the pGEM-T Easy vector and directly sequenced by Taq polymerase-based chain terminator method. Sequencing analysis indicated that both loci are complex repeats, TGrI29 containing two types of variable motifs (tC)n and (tg)n, and TGrI30 a tetra-nucleotide tandem units (atcc)n. In two TGrI29 alleles and one TGrI30 allele were found two different subtypes in each one, with the same molecular weights but different distribution of the tandem repeats. In conclusion, both microsatellites analyzed are highly informative polymorphic markers and can be used in linkage studies in families with congenital hypothyroidism or autoimmunity thyroid diseases.